Gastric decontamination performed 5 min after the ingestion of temazepam, verapamil and moclobemide: charcoal is superior to lavage - Lapatto-reiniluoto, O (Blackwell Science Inc, 2000)
AIMS: The aim was to study the efficacy of gastric lavage and activated charcoal in preventing the absorption of temazepam, verapamil and moclobemide when gastric decontamination was performed immediately after ingestion of the drugs. METHODS: Nine healthy volunteers took part in a randomized cross-over study with three phases. The subjects were administered single oral doses of 10 mg temazepam, 80 mg verapamil and 150 mg moclobemide. Five minutes later, they were assigned to one of the following treatments: 200 ml water (control), 25 g activated charcoal as a suspension in 200 ml water or gastric lavage. Plasma concentrations and the cumulative excretion into urine of the three drugs were determined up to 24 h. RESULTS: The mean AUC(0,24 h) of temazepam, verapamil and moclobemide was reduced by 95.2% (P < 0.01), 92.8% (P < 0.01) and 99.7% (P < 0.01), respectively, by activated charcoal compared with control. Gastric lavage did not reduce significantly the AUC(0,24 h) of these drugs. The 24 h cumulative excretion of temazepam, verapamil and moclobemide into urine was reduced significantly (P < 0.05) by charcoal but not by gastric lavage. Charcoal reduced the AUC(0,24 h), C(max) and urinary excretion of all three drugs significantly more than lavage. CONCLUSIONS: Activated charcoal is very effective and gastric lavage can be rather ineffective in preventing the absorption of temazepam, verapamil and moclobemide when the treatment is given very rapidly after ingestion of the drugs, before tablet disintegration has occurred.